-3=6(f-5)

Simple and best practice solution for -3=6(f-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=6(f-5) equation:


Simplifying
-3 = 6(f + -5)

Reorder the terms:
-3 = 6(-5 + f)
-3 = (-5 * 6 + f * 6)
-3 = (-30 + 6f)

Solving
-3 = -30 + 6f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-6f' to each side of the equation.
-3 + -6f = -30 + 6f + -6f

Combine like terms: 6f + -6f = 0
-3 + -6f = -30 + 0
-3 + -6f = -30

Add '3' to each side of the equation.
-3 + 3 + -6f = -30 + 3

Combine like terms: -3 + 3 = 0
0 + -6f = -30 + 3
-6f = -30 + 3

Combine like terms: -30 + 3 = -27
-6f = -27

Divide each side by '-6'.
f = 4.5

Simplifying
f = 4.5

See similar equations:

| 12/7=27/14a | | 6x-3(x-8)=4(x-7)+6 | | x^4-9x-3=0 | | 16x-19=133-6 | | 4x-(m+10)=60 | | -9(-4)+7=25+2 | | 2(a+6)=22 | | 63/(x+2) | | -38/3=10/9y | | 4x^2-3x+11=9x+6 | | 5(2x+3)-2(x-4)=2x-1 | | 2(x+2)(x-4)4=0 | | -34=42+-4v | | (X+3)(X+4)(X+5)=0 | | (X-3)(Y+7)=0 | | 6(5-2y)-5(y+3)= | | 5x-(x-18)=6-2(x+15) | | x*(x+1)(x+2)(x+3)=0.5625 | | 4(2+3)-2y= | | X^3-3x^2+x+1=0 | | -16-8(2a+3)=23-2a | | 4(2+3)-2y=3(4y+3) | | -14x^3+9x^2-2=0 | | 3/2x=189/20 | | -19x+4=0 | | 2(4w-1)=-10(w-3)+4 | | 5(x+5)=27 | | 30-5x=-5 | | 3.14*x^5-6x^4-9=0 | | pi*x^5-6x^4-9=0 | | 5x+5=137-6x | | 6x=121-5x |

Equations solver categories